In quest of justice? Clinical prioritisation in healthcare for the aged. Issue 4 (28th March 2008) - Pedersen, R; Nortvedt, P; Nordhaug, M; Slettebø, Å; Grøthe, K H; Kirkevold, M; Brinchmann, B S; Andersen, B
Abstract : Background: A fair distribution of healthcare services for older patients is an important challenge, but qualitative research exploring clinicians' consideration in daily clinical prioritisation in healthcare services for the aged is scarce. Objectives: To explore what kind of criteria, values, and other relevant considerations are important in clinical prioritisations in healthcare services for older patients. Design: A semi-structured interview-guide was used to interview 45 clinicians working with older patients. The interviews were analysed qualitatively using hermeneutical content analysis and template organising style. Participants: 20 physicians and 25 nurses working in public hospitals and nursing homes in different parts of Norway. Results and interpretations: Important dilemmas relate to under-provision of community care and comprehensive approaches, and over-utilisation of certain specialised services. Overt ageism is generally not reported, but the healthcare services for the aged seem to be inadequate due to more subtle processes, for example, dominating considerations and ideals and operating conditions that do not pay sufficient attention to older patients' needs and considerations of justice. Clinical prioritisations are described as being dominated by adapting traditional biomedical approaches to the operating conditions. Many of the clinicians indicate that there is a potential for improving end of life decisions and for reducing exaggerated use of life-prolonging treatment and hospitalisations. Conclusion: The interviews in this study indicate that considerations of justice and patients' perspectives should be given more attention to strike a balance between specialised medical approaches and more general and comprehensive approaches in healthcare services for older patients.